LARVICIDAL EFFECTS OF LUFFA AEGYPTIACA (MILL, 1638) ON CULEX QUINQUEFASCIATUS (SAY, 1823) (FUDMA JOURNAL OF SCIENCES, 2023)
Larvicidal effects of Luffa aegyptiaca was investigated on laboratory bred Culex quinquefasciatus from Zaria. Pulverized seed, stem, sponge and leaves of Luffa aegyptiaca, were extracted with methanol in a Soxhlet extractor. Extracts were diluted in borehole water and tested for larvicidal effects on medically important Culex quinquefasciatus mosquito under laboratory conditions. Hundred mosquito larvae (in four replicates of twentyfive each), in small white plastic disposable cups were exposed to concentrations of 0.0 mlL-1 [Control], 0.8mlL-1, 0.4mlL-1, 0.2mlL-1 and 0.1m1L-1 of seed, stem, sponge and leaves of Luffa aegyptiaca extracts for 24 hours to determine larval mortality. At 0.8mlL-1, 0.4mlL-1, 0.2mlL-1 and 0.1m1L-1 concentration of the seed extract, percentage larval mortality recorded were 95%, 77%, 61% and 48% respectively. At 0.8mlL-1, 0.4mlL- 1, 0.2mlL-1 and 0.1m1L-1 concentration of the stem extract, percentage larval mortality recorded were 20%, 4%, 0% and 0% respectively. At 0.8mlL-1, 0.4mlL-1, 0.2mlL-1 and 0.1m1L-1 concentration of the sponge extract, 76%, 59%, 42% and 30% larval mortality were recorded respectively. Zero mortality (0%) was recorded in groups exposed to different concentrations of leaf extract. Probit analyses of the larval mortality data gave LC50 values of 0.13mlL-1, 1.13mlL-1 and 0.26m1L-1 for the seed, stem and sponge extracts of the plant respectively. Our data suggests that leaf extract of Luffa aegyptiaca is not a good candidate for vector control, however, the seed, stem and sponge could be harnessed in vector control of noxious mosquito species of Culex quinquefasciatus to stem their disease transmission roles.
Keywords: Culex quinquefasciatus, leaf, larvae, Luffa aegyptiaca, seed, sponge